Analisa Kelayakan Finansial Perencanaan Tempat Pengolahan Sampah Berbasis 3R (Reduce, Reuse, Recycle) di Kecamatan Bangil Kabupaten Pasuruan - Rachmawati, Vitha (Pascasarjana Teknik Sipil Institut Teknologi Nasional Malang, 2025)
The increasing population in Bangil District, Pasuruan Regency, has resulted in an increase in waste generation, reaching 424.53 tons/year. Waste management is certainly necessary to maintain a clean and beautiful environment. Waste management through the 3R concept (Reduce, Reuse, Recycle) is one of the strategic solutions to reduce the volume of waste entering the Final Processing Site (TPA). This study aims to analyze the financial feasibility of planning a 3R waste processing site (TPS) in three densely populated sub-districts: Kolursari, Kidul Dalem, and Pogar. The research methods include a survey of waste generation and composition, land requirements analysis, preparation of a budget plan (RAB), and financial feasibility analysis using Net Present Value (NPV) and Benefit Cost Ratio (BCR) indicators with a 10% discount rate and a 10-year project life. The planning results show a land requirement of 976.05 m² with a RAB of Rp 645,171,893,- with revenue from waste levies and waste sales per year of Rp 1,194,866,460,- and operational expenses per year of Rp 428,133,600,-. The NPV value obtained is Rp 4,066,069,249 > 0 and BCR 2.24 > 1, indicating that the project is financially feasible.